How do mobile games connect us? a perspective on social media affordances - Zhao, Fan; Alsagoff, Syed Agil; Abdullah, Karmilah (Penerbit Universiti Kebangsaan Malaysia, 2025)
Games as a "third place" for public interaction have attracted growing academic attention, particularly with their integration into the new media environment, which grants them enhanced media functions and deeper social significance. This study explores how and under what conditions mobile games effectively connect player communities, drawing on the perspective of Social Media Affordances. A walkthrough method and in-depth interviews with 19 Honor of Kings players were employed to examine this phenomenon. The findings indicate that mobile games utilize interface interactions, platform algorithms, and voice media affordances to provide conditions for identity perception, relational connectivity, and contextual imagination, thereby facilitating social interactions. However, these conditions are not universally applicable to all players. Instead, they are influenced by individual media usage behaviors and subjective agency, characterized by variability, instability, and reciprocal relationships. This study highlights the co-construction of social affordances in mobile games by media technologies and player interactions. It uncovers the intrinsic logic and value of mobile games as emerging social media platforms and extends the application of affordance theory to the domain of game-based social interactions. By examining the interplay between technological affordances and user practices, this research provides a deeper understanding of mobile games' role in shaping social connectivity in the digital age.